Stereoselective addition of Grignard reagents to (2-methyl-5-tert-butyl)phenyl 1-thio-β-D-ribopentodialdo-1, 4-furanoside derivative. Issue 16 (20th April 2017) - Ren, Huanming; Xie, Wuchen; Xiong, Bing; Shen, Jingkang; Chen, Guohua; Chen, Yue-Lei
Abstract: Addition of a wide range of Grignard reagents to acetone protected (2-methyl-5- tert -butyl)phenyl 1-thio- β -D -ribopentodialdo-1, 4-furanoside3b produced useful 5( R ) C -substituted products with moderate to good yields, and moderate to perfect stereoselectivities, with no need of additives. n.O.e. Analysis of3b showed that 1- S -aryl group could contribute to the stereoselectivity of addition reaction. The stereochemistry of 4 representative 5- C -substituted ribofuranoside products was further confirmed by NMR study of corresponding Mosher esters, by chemical derivatization, or by single crystal study. Graphical abstract: